(untitled) (International Journal of Psychosocial Rehabilitation, 2020)
The present research is conducted to identify the effects of workplace stress on mental well-being among marketing executives of select private banks of Punjab state of India through a sample of 600 executives. Regression technique was applied to observe the effects of workplace stress on mental health, and it was found to be positive. This paper presents the dimensions of how the mental health of executives is impacted by workplace stress and discusses the managerial implications for better working organizations.